The Effect of Magnetic Induction on Seeds Infected Fusarium Sp. Toward Generative Growth of Red Chili (Capsicum annuum. L) - Rochmah Agustrina; Berekhya Glori Hernawati; Yulianty Yulianty; Bambang Irawan (Department of Biology Faculty of Mathematics and Natural Sciences Universitas Lampung in collaboration with The Indonesian Association of Biology (PBI) Lampung Branch., 2019)
Magnetic fields are proven to improve the quality of growth of various plants. In the study, it was examined whether the treatment of magnetic fields on chili seeds (Capsicum annuum. L) infected by Fusarium sp. could maintain plant growth to the generative phase. This research is two-factor research using a randomized block design. The first factor is the 0.2 mT magnetic field induction treatment consisting of 7 minutes 48 seconds (M7), 15 minutes 36 seconds (M15) and control (M0) as control and the second factor is the Fusarium oxysporum infection treatment consisting of 60 minutes infected (F60) and not infected (F0). Each treatment unit was repeated 5 times. Data obtained were analyzed for variance at a 5% significance level. The results of the analysis showed that the treatments in this study did not provide significant differences in carbohydrate content, flowering speed and number of flowers, as well as the fruiting rate of plants from seeds infected with Fusarium sp (M0F60, M7, F60, and M15F60), thus the magnetic field treatment could be causing plants to be resistant to Fusarium sp. so plants from seeds infected with Fusarium sp. able to flower and bear fruit at the same speed and produce the same amount of interest.